ANALISIS DETERMINAN PROFITABILITAS PERUSAHAAN SEKTOR TEKNOLOGI DI NASDAQ - Lianita Dian Rahmawati; I Gusti Ketut Agung Ulupui; Nuramalia Hasanah (LPPM Politeknik Pratama, 2023)
The development and widespread use of technology has made the technology sector one of the most profitable industries in the world. The company's ability to generate profits, often referred to as profitability, is very important for every company. The goal of this study is to investigate the variables that are thought to affect (become a determinant of) the profitability of technology sector companies in NASDAQ. As the first electronic-based stock exchange in the world, NASDAQ widely chooses by technology companies to conduct IPOs. The samples in this study were taken using purposive sampling techniques. This study is quantitative research and uses secondary data in its testing. The factors tested include Liquidity, Capital Structure, Sales Growth, and Working Capital Turnover. Data were tested using multiple linear regression analysis models or techniques and processed using SPSS software version 24. The research test results of the study showed that liquidity; capital structure; and sales growth partially have a positive effect on the profitability of technology sector companies in NASDAQ, while working capital turnover has no effect on the profitability of technology sector companies in NASDAQ.